Międzynarodowa ochrona praw człowieka w kontekście zjawiska handlu ludźmi - Szymański, Łukasz (Polityka i Społeczeństwo, 2020)
The subject of this study is the international protection of human rights in the context of human trafficking and slavery. Human trafficking and slavery are one of the most vivid examples of the violation of the individual's right to freedom, integrity and security, and of the denial of human dignity, which is the main pillar of the international system for the protection of human rights. Therefore, trade in live goods and other crimes related to the exploitation of prostitution have become the subject of several international conventions. International communities have decided to prevent and combat this phenomenon with the help of criminal law instruments. The study contains explanations of statutory concepts related to the protection of human rights and human trafficking. In addition, it discusses the forms of protection of human rights. The theoretical nature of this paper is based on publications in the field of international law, criminal law, and constitutional law.